SP0056 Potential therapeutic use of micrornas in rheumatology. (23rd January 2014) - Jäck, H.-M.; Porstner, M.; Wittmann, J.; Bösl, M.
Abstract : Our long-term goal is to understand how small non-coding micro-RNAs (miRNAs) regulate and fine-tune the differentiation of mature B cells into memory B cells and antibody-secreting plasma cells. miRNAs control the expression of specific target genes at the post-transcriptional level by binding to target sequences e.g., in the 3'-untranslated region of mRNAs, which results either in a block of translation or an accelerated degradation of the respective target mRNA. Lineage-specific deletion of the miRNA-processing DICER protein as well as of individual miRNAs revealed the importance of miRNA pathway in early steps of central B cell maturation. However, the mechanisms by which miRNA-dependent circuits control the antigen-induced phase of B cell activation of mature naive B cells and their subsequent differentiation into effector cells remain largely elusive. To change this situation we established a transgenic knock-in mouse line with a floxed allele of DGCR8, an essential subunit of the nuclear miRNA processing complex. B cell-specific deletion of DGCR8 resulted in a complete maturation block at the pro-B stage, indicating that miRNA processing is essential for central B cell maturation. We have also obtained genome-wide miRNA expression profiles of all major mouse B cell subsets, including long-lived plasma cells, and found a profound upregulation of miR-ER3 in plasma cells. Ectopic expression of this plasma cell signature miRNA in primary mouse B cells accelerated the differentiation into antibody-secreting plasmablast, as indicated by upregulation of CD138 and enhanced secretion IgM secretion. We also verified several miR-ER3 targets, e.g., Bach2 and MiTF, that are part of the transcriptional circuit that controls germinal center reactions and plasma cell differentiation. These studies will provide new molecular insights into regulatory circuits that control the production of antibodies and could potentially lead to new avenues for diagnosing or treating diseases associated with aberrant plasma cell development, e.g., primary antibody deficiencies, plasma cell malignancies, and autoimmune disorders. Disclosure of Interest: None Declared